MUSEQuBES: Unveiling Cosmic Web Filaments at z ≈ 3.6 through Dual Absorption and Emission Line Analysis - Eshita Banerjee; Sowgat Muzahid; Joop Schaye; Sebastiano Cantalupo; Sean D. Johnson (The Astrophysical Journal Letters)
According to modern cosmological models, galaxies are embedded within cosmic filaments, which supply a continuous flow of pristine gas, fueling star formation and driving their evolution. However, due to their low density, the direct detection of diffuse gas in cosmic filaments remains elusive. Here, we report the discovery of an extremely metal-poor ([ X / H ] ≈ −3.7), low-density ( ${log}_{10}{n}_{{\rm{H}}}/{{\rm{cm}}}^{-3}\,≈ $ −4, corresponding to an overdensity of ≈5) partial Lyman limit system (pLLS) at z ≈ 3.577 along the quasar sightline Q1317–0507, probing cosmic filaments. Additionally, two other low-metallicity ([ X / H ] ≲ −2) absorption systems are detected at similar redshifts, one of which is also a pLLS. Very Large Telescope (VLT) MUSE observations reveal a significant overdensity of Ly α emitters (LAEs) associated with these absorbers. The spatial distribution of the LAEs strongly suggests the presence of an underlying filamentary structure. This is further supported by the detection of a large Ly α -emitting nebula with a surface brightness of $\geqslant 1{0}^{-19}\,erg\,{cm}^{-2}\,{{\rm{s}}}^{-1}\,{arcsec}^{-2}$ , with a maximum projected linear size of ≈260 pkpc extending along the LAEs. This is the first detection of giant Ly α emission tracing cosmic filaments, linked to normal galaxies and likely powered by in situ recombination.